Bi3+‐Er3+ and Bi3+‐Yb3+ Codoped Cs2AgInCl6 Double Perovskite Near‐Infrared Emitters. Issue 28 (31st March 2020) - Arfin, Habibul; Kaur, Jagjit; Sheikh, Tariq; Chakraborty, Sudip; Nag, Angshuman
Abstract: Bi 3+ and lanthanide ions have been codoped in metal oxides as optical sensitizers and emitters. But such codoping is not known in typical semiconductors such as Si, GaAs, and CdSe. Metal halide perovskite with coordination number 6 provides an opportunity to codope Bi 3+ and lanthanide ions. Codoping of Bi 3+ and Ln 3+ (Ln=Er and Yb) in Cs2 AgInCl6 double perovskite is presented. Bi 3+ ‐Er 3+ codoped Cs2 AgInCl6 shows Er 3+ f‐electron emission at 1540 nm (suitable for low‐loss optical communication). Bi 3+ codoping decreases the excitation (absorption) energy, such that the samples can be excited with ca. 370 nm light. At that excitation, Bi 3+ ‐Er 3+ codoped Cs2 AgInCl6 shows ca. 45 times higher emission intensity compared to the Er 3+ doped Cs2 AgInCl6 . Similar results are also observed in Bi 3+ ‐Yb 3+ codoped sample emitting at 994 nm. A combination of temperature‐dependent (5.7 K to 423 K) photoluminescence and calculations is used to understand the optical sensitization and emission processes. Abstract : Bi 3+ ‐Ln 3+ (Ln=Er, Yb) codoping imparts optical functionality to Cs2 AgInCl6 double perovskite. Bi 3+ tailors optical absorption, thereafter non‐radiatively exciting Er 3+ or Yb 3+ f‐electrons, which then de‐excite by emitting 1540 and 994 nm near‐infrared (NIR) light, respectively.